To inform and engage: museum websites and dynamic delivery of information - Zeljkovic, Nada (Curtin University, 2002)
The World Wide Web has emerged as a powerful communications medium. With the development of new technologies, organizational websites are getting bigger and more complex, using design elements such as sound and motion to engage users' attention. This project will look at how users respond to the ways designers and developers present information on the web in a dynamic form which incorporates sound and motion. The research will focus on evaluating the communicative effectiveness of websites (particularly websites with different degrees of dynamic content in them), and will see if certain ways of presenting dynamic content are more effective than others. The method used will consist of observing users while they try to accomplish specific tasks on selected websites, through interviews, questionnaires and through verbal protocol ('think aloud') analysis. Effectiveness will be measured by such things as how long it takes them to complete each task, how successful they were in finding the necessary information, and the ease of use. Other factors which provide possible explanations for differences in effectiveness will also be measured; these will be drawn from two theoretical bases: communication theory (Fiske, 1982) and social psychology (Ajzen, 1991; Klobas & Morrison, 1999). The outcome of the research will be identification of problem areas associated with the effectiveness of information delivery by dynamic sites. Guidelines for communication designers, information architects and developers of websites, as they evaluate the success of dynamic sites, will be an appendix to the research.